Characterization of fusion welded joint: a review - Che Lah, Nur Azida; Ali, Aidy; Ismail, Napsiah (Universiti Putra Malaysia Press, 2009)
Welding process is most widely used in joining components or structures in industry. Although welding is part of a larger category called metals joining, the weld itself still gives significant problems to engineers, researchers and manufacturers until today. Several widely used welding processes, such as the Metal Inert Gas (MIG), Tungsten Inert Gas (TIG), and Manual Metal Arc (MMA), were studied. In the present paper, the characterization of the macrostructure, microstructure, hardness and residual stress distribution are highlighted and discussed to achieve a better understanding of the welded quality which is crucial in determining the welded products.